A Literature Review on Tourism Communication in the Tourism Village of Penglipuran: A Perspective on Artificial Intelligence-Based Immersive Storytelling - Wida Nofiasari; Ahmad Mulyana; Nurhayani Saragih (Enrichment: Journal of Multidisciplinary Research and Development, 2026)
This research aims to analyze the development of tourism communication concepts based on immersive storytelling in the preservation of cultural identity in Penglipuran Tourism Village, Bali. The approach used in this research is qualitative, employing a literature review method. Data were collected from various relevant scientific literature, books, and journal articles, then analyzed using content analysis and thematic analysis techniques through a process of theoretical synthesis. The results show that the transformation of tourism communication has shifted from an informative model toward a narrative and experiential communication model grounded in digital technology. AI-based immersive storytelling enables tourists to experience cultural narratives in a more in-depth, interactive, and contextual manner without directly disturbing sacred cultural practices. This technology also has the potential to reduce the pressure of mass tourism through educational virtual experiences. However, risks remain, including cultural simplification, algorithmic bias, and the dominance of market logic, which may erode the authentic meaning of local culture. This study concludes that AI-based immersive storytelling holds significant potential for preserving cultural identity when developed in an ethical and participatory manner, grounded in kearifan lokal (local wisdom). The implications of this study underscore the importance of a digital ethics-based tourism communication model that positions local communities as the primary agents in the production of cultural narratives, in order to sustain cultural continuity and sovereignty in the digital era